Enhanced tunability of a multiwavelength Brillouin-Erbium laser using cascaded photonic crystal and large effective area fibers - Ramzia Salem, A.M.; Ramli, R.; Alresheedi, M.T.; Zainol Abidin, N.H.; Ng, E.K.; Mahdi, M.A. (Academic Press Inc., 2025)
This work demonstrates a wideband multiwavelength laser using bismuth-based erbium-doped fiber with fiber coils of photonic crystal fiber (PCF) and a large effective area fiber (LEAF) in cascaded configuration. The generation of the multiwavelength laser was based on the stimulated Brillouin scattering effect. The tunability of the laser-based PCF that was initially limited due to four-wave mixing induced spectral broadening was enhanced by adding a coil of LEAF. A flawless tuning range in the L-band spanning 53 nm was achieved with a set of six laser lines. This multiwavelength laser could be tuned from 1567 to 1620 nm at 350 mW pump power and 5 mW Brillouin pump power. The generated output channels were very stable, showing a maximum peak power fluctuation of 0.75 dB over the duration of 60 min. This work showcases a technique to enhance the tuning range of Brillouin-based lasers for photonics applications in general.